Maya Medicine : Traditional Healing in Yucatán - Kunow, Marianna Appel, 1958- (Book collections on Project MUSE., 2003)
"This book traces the entire process of curing. The author collected plants with traditional healers and observed their techniques including prayer and massage as well as plant medicine, western medicine, and ritual practices. Plant medicine, she found, was the common denominator, and her book includes information of the plants she worked with and studied"--Book jacket.